Expression profiling of various genes during the fruit development and ripening of mango - Pandit, Sagar S.; Kulkarni, Ram S.; Giri, Ashok P.; Koellner, Tobias G.; Degenhardt, Joerg; Gershenzon, Jonathan; Gupta, Vidya S. (Plant Physiology and Biochemistry, 2010)
Mango (Mangifera indica L. cv. Alphonso) development and ripening are the programmed processes; conventional indices and volatile markers help to determine agronomically important stages of fruit life (fruit-setting, harvesting maturity and ripening climacteric). However, more and precise markers are required to understand this programming; apparently, fruit's transcriptome can be a good source of such markers. Therefore, we isolated 18 genes related to the physiology and biochemistry of the fruit and profiled their expression in developing and ripening fruits, flowers and leaves of mango using relative quantitation PCR. In most of the tissues, genes related to primary metabolism, abiotic stress, ethylene response and protein turnover showed high expression as compared to that of the genes related to flavor production. Metallothionin and/or ethylene-response transcription factor showed highest level of transcript abundance in all the tissues. Expressions of mono- and sesquiterpene synthases and 14-3-3 lowered during ripening; whereas, that of lipoxygenase, ethylene-response factor and ubiquitin-protein ligase increased during ripening. Based on these expression profiles, flower showed better positive correlation with developing and ripening fruits than leaf. Most of the genes showed their least expression on the second day of harvest, suggesting that harvesting signals significantly affect the fruit metabolism. Important stages in the fruit life were clearly indicated by the significant changes in the expression levels of various genes. These indications complemented those from the previous analyses of fruit development, ripening and volatile emission, revealing the harmony between physiological, biochemical and molecular activities of the fruit. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Mangifera indica; Stress response; Terpene metabolism; Transcriptome analysis

Evaluation of genetic variability in Symplocos laurina Wall. from two biodiversity hotspots of India - Bhagwat, Rasika M.; Banu, Sofia; Dholakia, Bhushan B.; Kadoo, Narendra Y.; Lagu, Meena D.; Gupta, Vidya S. (Plant Systematics and Evolution, 2014)
Symplocos laurina Wall., an important medicinal tree species, is one of the pioneering plants for establishment of shola forest ecosystem. We analyzed 208 accessions of S. laurina from 13 populations belonging to three ecoregions in India namely, Western Ghats, Eastern Ghats and Northeast India, to comment on the genetic diversity and population structure of the species. Of the 100 inter simple sequence repeat primers screened, eight were selected based on their clear and reproducible polymorphic patterns. These eight ISSR primers produced on an average 1,014 bands from 208 accessions, of which 6.58 % were rare bands, 55.96 % were shared bands and 37.46 % were similar bands. The primers, UBC835 and UBC880, amplified the highest number of polymorphic loci (16), while the primer UBC852 amplified the least number of amplicons (9). The values for total genetic diversity (H-T) and the average heterozygosity (H-S) were 0.3407 and 0.2263, respectively; while the coefficient of genetic differentiation (G(ST)) was 0.3358. Within-population variance was higher (68 %) than among-population variance (17 %), indicating high intra-population genetic diversity. These populations were grouped according to their geographical location in cluster analysis. Mantel test also showed significant positive correlation between genetic and geographical distances. The present study revealed the importance of the Palghat gap in South India in shaping the distribution of genetic diversity in S. laurina.
Keywords: Biodiversity hotspots; Genetic diversity; ISSR; Palghat gap; Symplocos laurina

Ecological turmoil in evolutionary dynamics of plant-insect interactions: defense to offence - Mishra, Manasi; Lomate, Purushottam R.; Joshi, Rakesh S.; Punekar, Sachin A.; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
Available history manifests contemporary diversity that exists in plant-insect interactions. A radical thinking is necessary for developing strategies that can co-opt natural insect-plant mutualism, ecology and environmental safety for crop protection since current agricultural practices can reduce species richness and evenness. The global environmental changes, such as increased temperature, CO (2) and ozone levels, biological invasions, land-use change and habitat fragmentation together play a significant role in re-shaping the plant-insect multi-trophic interactions. Diverse natural products need to be studied and explored for their biological functions as insect pest control agents. In order to assure the success of an integrated pest management strategy, human activities need to be harmonized to minimize the global climate changes. Plant-insect interaction is one of the most primitive and co-evolved associations, often influenced by surrounding changes. In this review, we account the persistence and evolution of plant-insect interactions, with particular focus on the effect of climate change and human interference on these interactions. Plants and insects have been maintaining their existence through a mutual service-resource relationship while defending themselves. We provide a comprehensive catalog of various defense strategies employed by the plants and/or insects. Furthermore, several important factors such as accelerated diversification, imbalance in the mutualism, and chemical arms race between plants and insects as indirect consequences of human practices are highlighted. Inappropriate implementation of several modern agricultural practices has resulted in (i) endangered mutualisms, (ii) pest status and resistance in insects and (iii) ecological instability. Moreover, altered environmental conditions eventually triggered the resetting of plant-insect interactions. Hence, multitrophic approaches that can harmonize human activities and minimize their interference in native plant-insect interactions are needed to maintain natural balance between the existence of plants and insects.
Keywords: Climatic change; Co-evolution; Ecosystem; Human interference; Plant-insect interaction

Expression of proteins involved in digestion and detoxification are regulated in helicoverpa armigera to cope up with chlorpyrifos insecticide - Dawkar, Vishal V.; Chikate, Yojana R.; More, Tushar H.; Gupta, Vidya S.; Giri, Ashok P. (Insect Science, 2016)
Helicoverpa armigera is a key pest in many vital crops, which is mainly controlled by chemical strategies. To manage this pest is becoming challenging due to its ability and evolution of resistance against insecticides. Further, its subsequent spread on nonhost plant is remarkable in recent times. Hence, decoding resistance mechanism against phytochemicals and synthetic insecticides is a major challenge. The present work describes that the digestion, defense and immunity related enzymes are associated with chlorpyrifos resistance in H. armigera. Proteomic analysis of H. armigera gut tissue upon feeding on chlorpyrifos containing diet (CH) and artificial diet (AD) using nano-liquid chromatography-mass spectrometry identified upregulated 23-proteins in CH fed larvae. Database searches combined with gene ontology analysis revealed that the identified gut proteins engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification. Biochemical and quantitative real-time polymerase chain reaction analysis of candidate proteins indicated that insects were struggling to get nutrients and energy in presence of CH, while at the same time endeavoring to metabolize chlorpyrifos. Moreover, we proposed a potential processing pathway of chlorpyrifos in H. armigera gut by examining the metabolites using gas chromatography-mass spectrometry. H. armigera exhibit a range of intriguing behavioral, morphological adaptations and resistance to insecticides by regulating expression of proteins involved in digestion and detoxification mechanisms to cope up with chlorpyrifos. In these contexts, as gut is a rich repository of biological information; profound analysis of gut tissues can give clues of detoxification and resistance mechanism in insects.
Keywords: chlorpyrifos; Helicoverpa armigera; insecticide resistance; proteomics; real-time PCR

Effect of postharvest ethylene treatment on sugar content, glycosidase activity and its gene expression in mango fruit - Chidley, Hemangi G.; Deshpande, Ashish B.; Oak, Pranjali S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2017)
BACKGROUND: Ripening-associated softening is one of the important attributes that largely determines the shelf-life of mango (Mangifera indica Linn.) fruits. To reveal the effect of pre-climacteric ethylene treatment on ripening-related softening of Alphonso mango, ethylene treatment was given to mature, raw Alphonso fruits. Changes in the pool of reducing and non-reducing sugars, enzymatic activity of three glycosidases: ss-D-galactosidase, alpha-D-mannosidase and ss-D-glucosidase and their relative transcript abundance were analysed for control and ethylene treated fruits during ripening. RESULTS: Early activity of all the three glycosidases and accelerated accumulation of reducing and non-reducing sugars on ethylene treatment was evident. ss-D-Galactosidase showed the highest activity among three glycosidases in control fruits and marked increase in activity upon ethylene treatment. This was confirmed by the histochemical assay of its activity in control and ethylene treated ripe fruits. Relative transcript abundance revealed high transcript levels of ss-D-galactosidase in control fruits. Ethylene-treated fruits showed early and remarkable increase in the ss-D-galactosidase transcriptswhile alpha-D-mannosidase transcript variants displayed early accumulation. CONCLUSION: Thefindings suggest reduction in the shelf-life of Alphonso mango upon pre-climacteric ethylene treatment, a significant role of ss-D-galactosidase and alpha-D-mannosidase in the ripening related softening of Alphonso fruits and transcriptional regulation of their expression by ethylene. (C) 2016 Society of Chemical Industry